RANCANG BANGUN SISTEM INFORMASI MANAJEMEN KEUANGAN BERBASIS WEBSITE DENGAN METODE WATERFALL DI PT STRAWBERINDO LESTARI - Andika Hiro Pratama, (2023)
PT Strawberindo Lestari is a company engaged in the plantation sector located in Puncak. PT Strawberindo Lestari distributes berry products to various cities, especially supermarkets in the Jabodetabek area. Currently, PT Strawberindo Lestari still uses a manual system for recording financial transactions, which certainly slows down their business operations. This research was conducted using the waterfall method for system design, carried out by the author, and also utilized the Laravel framework and tailwind css to assist and expedite the author's performance in system development. The result of the research conducted by the author is a system that can input income, expenses, and cash activities, enabling the system to generate automated reports such as profit and loss statements and cash flow reports for the company. Through testing conducted by several users, the system performs well in displaying income and expense data, effectively storing data in the cloud, and automating the creation of financial reports, including profit and loss statements and cash flow reports for specific periods.